AGORA IX - alternative education and training processes. Thessaloniki, 26-27 june 2000 : Thessaloniki, 26 - 27 June 2000 - (:unkn) unknown (Office for Official Publications of the European Communities, 2003)
"Agora IX cast a critical eye on the paradoxes of the success achieved by alternative modes of training. Through this success they help filter out more young people (and less young people) who have experienced school failure and help create a hard core of those who are left by the wayside. How are we to fight school failure and allow every citizen access to the key skills considered indispensable in our society? Agora IX may not have found a miracle cure but it did stress the need to mobilise all 'intervention partners' (rather than actors), considering that the educational system now obviously goes beyond the school system. Lifelong learning should allow everyone to learn at their own speed. What remains to be done is to create the conditions for this learning and find the means to motivate citizens to pursue it." (Herausgeber, BIBB-Doku)
Keywords: P 1.7 Benachteiligte; P 2.1.1 Ohne Schulabschluss; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; I 2.2 Europa; Benachteiligter Jugendlicher; Schulabbrecher; Berufsausbildung; Berufliche Integration; Berufseinmündung; Erste Schwelle; Soziale Integration; Europa